Moderate Secularism in Practice: A Comparison of European and Muslim Countries - Frim-Abrams, Naomi; Kulvmann, Jesper (Journal of Southeast Asian Human Rights, 2025)
Multiculturalism has increasingly been identified with ethno-religious identities in recent years. Multiple authors paraphrase the interaction of multiculturalism and secularism as â€œmoderate secularism,â€ which emphasizes equal status of the majority and minority religions. In the academic realm, the discussion on moderate secularism has foremost been limited to Western countries, irrespective that this debate is particularly relevant in non-Western secular countries. This study widens the scope and compares to what degree Western and non-Western Muslim states allow religious minority groups to co-exist with the majority religions. Three European and three non-Western countries are included in the study based on a review of national policies and practices around secularism, analyzed through Modoodâ€™s framework of moderate secularism. This study finds that the position of minority religions is generally weakened in all the countries, with strong political tensions between different religious groups. While the European countries continue to assess the position of minority religion from a secular perspective, strengthening Christian identity, non-Western countries with strong Islamic constituencies gain more influence in political processes. This study also concludes that Modoodâ€™s model of moderate secularism is flawed, as it does not take into account political realities and public attitudes. Keywords: Moderate secularism, multiculturalism, immigration